2020
DOI: 10.14283/jpad.2020.70
|View full text |Cite
|
Sign up to set email alerts
|

A Web-Based Multidomain Lifestyle Intervention for Older Adults: The eMIND Randomized Controlled Trial

Abstract: Importance/Objective: To describe the feasibility and acceptability of a 6-month web-based multidomain lifestyle training intervention for community-dwelling older people and to test the effects of the intervention on both function- and lifestyle-related outcomes. Design: 6-month, parallel-group, randomized controlled trial (RCT). Setting: Toulouse area, South-West, France. Participants: Community-dwelling men and women, ≥ 65 years-old, presenting subjective memory complaint, without dementia. Intervention: Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
50
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(51 citation statements)
references
References 37 publications
1
50
0
Order By: Relevance
“…Furthermore, results were still statistically significant after multiple-comparison correction (p < 0.01 after Bonferroni correction). These findings should be confirmed in the multidomain intervention trials that are currently underway (35)(36)(37).…”
Section: Strengths and Limitationsmentioning
confidence: 75%
“…Furthermore, results were still statistically significant after multiple-comparison correction (p < 0.01 after Bonferroni correction). These findings should be confirmed in the multidomain intervention trials that are currently underway (35)(36)(37).…”
Section: Strengths and Limitationsmentioning
confidence: 75%
“…In papers in which four or more items were found to be ‘high risk’, through author agreement, we decided to exclude them as papers for systematic review and data ex-traction. Accordingly, a total of 11 papers [ 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 ] were included except Styliadis (2015) for systematic review and data extraction ( Figure 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…We identified studies with high heterogeneity by performing cumulative sensitive analysis. The study of de Souto Barreto [ 37 ] was identified with high heterogeneity. Therefore, in Figure 6 , a forest plot without de Souto Barreto’s study [ 37 ] is presented.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…While previous studies have emphasized on the need of resistance exercise and protein supplement, our study is the first to document improvement in gait speed, with reduction in the prevalence of SG and poor HGS after 3 months of dualtask exercise. While there are many studies evaluating web-based multi-domain interventions in the home setting, the inclusion of web-based dual-task exercises combined with resistance exercise, and protein enriched diet needs to studied to guide Public Health authorities on measures to prevent sarcopenia during future pandemics and lockdown (52).…”
Section: Discussionmentioning
confidence: 99%